THE FACTORS WHICH PREVENT PHYSICAL EDUCATION AND SPORT INSTRUCTOR CANDIDATE FROM JOINING RECREATIONAL ACTIVITIES(FIRAT UNIVERSITY EXAMPLE) - Nacar, Eyyup; Gacar, Atalay (My University, 2019)
The quality of life of individuals increase with the help of free time services that is provided in the society. Recreation is a tool that is more meaningful and filled for the life. The impoortance of submitting these services to the teachers who will bring up the prospect generations is known by the universities. Based on these considerations, In this study, it is aimed to scrutinize for the obctacles that hinder from participating recreational activitires in terms of some variations according to the student’s perceive by the candidates of Physical Education and Sport Insructor.In the scope of investigation; In the school year of 2018-2019 , those deserving Instructor Nominee from 308 people, selected by random sampling method,who belongs to Physical Education, Sport Instructor, coaching, Sports Management and Recreation Departmants by taking pedagogical formation account for 182Instructor Nominees, willing toparticipate for inveestigation, and form our sample group.Data collection tool which is used in the research consists of two sections. In the first section, participants’ individual knowledge are intended to explain.In the second section, Being formed 6 sub dimensions and 27 articles, ‘’Leisure Barriers’’ scale developed by Alexandris and Carroland of validity and reliability studies done by Karaküçük and Gürbüz has been utilized. SPSS package statistics program has been used for analyzes obtained from the research. Frequency distribution, arithmetic average, percentages, t test and One -Way Anova are used for the results by means of SPSS, while on the significant differences in results Tukey test are benefited to determine the differences among which groups. Fail level is taken as (p<0,05). In consequence of our study, Physical Education and Sport Insructor candidate’s sex and education studied according to the department variable not participating the activities has not been observed with meaningful difference when distribution level of sub dimensions analyzed (p>0,05.)Significant differences were observed according to age and leisure activity area variables (p<0,05.)When Physical Education and Sports Teacher Candidates not participating in recreational activities are examined, Facilities / Service sub-dimension are observed much higher than Individual Psychology, lack of Knowledge, lack offFriends, time, interest deficiency sub-dimensions In consequence of our study, the inadequacy of facilities in the university and facility service in terms of participants,are regarded as one of the biggest reasons for not participating in recreational activities
Keywords: Eğitim; Eğitim Araştırmaları